Assessment of quality of life as an element of monitoring health status in children and adolescents with type 1 diabetes mellitus - Nina Viktorovna Bolotova (Endocrinology Research Centre, 2009)
Aim. To assess quality of life (QL) in children and adolescents with type 1 diabetes mellitus (DM1) depending on its duration, mode of insulin administration,and degree of social adaptation. Materials and methods. Generic Core Scale and Diabetes Module of Pediatric Quality of Life Questionnaire were used to estimate QL in 72 diabeticchildren and adolescents aged 5-18 yr with the participation of one of the parents. Patients with severe concomitant pathology were not includedin the study. Results. Overall QL score in children and adolescents with DM1 was 73,043?1,24. The psycho-social activity of most patients in all age groups was ratherhigh in contrast to suppressed physical functions due to complications of DM1 ten or more years in duration (51,4?9,19 scores). The psycho-emotionalstate was less dependent on negative effects of the disease. Patients using an insulin pump had on the whole better QL than those receiving intensiveinsulin therapy (82 and 72 points respectively, p